Media piracy in the Middle East: A case study of 2018 world cup - Sayed, Ruba (AUC Knowledge Fountain, 2019)
The main aim of this dissertation is to study the audience's perception, awareness, behavior and attitude towards pirating live sports broadcasting media content in one of the Middle Eastern countries, which is Egypt. Moreover, this research fills a gap in the literature by investigating the media landscape in the Middle East in the age of digitalization, presenting an overview of media piracy, internet penetration and social media usage in the region in general and in Egypt in specific. It also studies the recent piracy activity in the case of 2018 FIFA World Cup in Egypt, by examining the legal and illegal broadcasters in the Middle East. Hence, the core of this study is the Egyptian media audiences and football fans who watched the 2018 tournament either by using legal methods which are subscribing to beIN sports packages, since it was the only legal broadcaster in the region, or using other illegal techniques such as illegal television cables and illegal live streaming from the internet. The study is conducted on a purposive sample of 460 young Egyptians; their age varies between 18-30 based on previous statistics, which revealed that the millennials in MENA are the ones who violate the intellectual property of the media the most and they are altering the media landscape in the region. The research follows a triangulation method by combining two research approaches; in-depth interviews as a qualitative methodology and surveys as a quantitative one. The theoretical framework used in this study is the Theory of Planned Behavior and Social Responsibility Theory. Also, this study revealed several different important factors that are related to pirating sports broadcasting media content, which are: 1) the impact of Egyptian youth on this phenomenon, 2) the factors that influence their intentions and behaviors to violate the intellectual property of the media, 3) the techniques that could be used to reduce piracy, 4) the audience awareness about this issue and the relationship between being a football fan and the size of sports pirated content, and 5) the correlation between the economic status of the audiences and the act of media piracy. Thus, the study at hand managed to outline the behavior of the Egyptian youth towards pirating the media.